2018
DOI: 10.1186/s12885-018-4342-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic polymorphisms CYP2A6*2 rs1801272 and CYP2A6*9 rs28399433 with tobacco-induced lung Cancer: case-control study in an Egyptian population

Abstract: BackgroundSeveral studies have reported the role of CYP2A6 genetic polymorphisms in smoking and lung cancer risk with some contradictory results in different populations. The purpose of the current study is to assess the contribution of the CYP2A6*2 rs1801272 and CYP2A6*9 rs28399433 gene polymorphisms and tobacco smoking in the risk of lung cancer in an Egyptian population.MethodsA case-control study was conducted on 150 lung cancer cases and 150 controls. All subjects were subjected to blood sampling for Extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Again, our result showed no significant difference between this SNP and the sensitivity or the response to warfarin during the initial or stabilization phase of therapy. The frequency of minor alleles of CYP2A6 rs1801272 SNP in our population was 1.5%, which was consistent with that found in African-American and Brazilian ethnic groups with 1.1% and 1.7%, respectively, and it was less than what was found in the Chinese population with 2.2% and more than Egyptian and Japanese population with 0.7% and 0.0%, respectively 54 . According to the study conducted in the Canadian population, patients with allelic polymorphisms (T) variants are associated with a greater sensitivity to warfarin and, therefore, lead to a significant reduction in the weekly dose of warfarin 55 .…”
Section: Discussionsupporting
confidence: 90%
“…Again, our result showed no significant difference between this SNP and the sensitivity or the response to warfarin during the initial or stabilization phase of therapy. The frequency of minor alleles of CYP2A6 rs1801272 SNP in our population was 1.5%, which was consistent with that found in African-American and Brazilian ethnic groups with 1.1% and 1.7%, respectively, and it was less than what was found in the Chinese population with 2.2% and more than Egyptian and Japanese population with 0.7% and 0.0%, respectively 54 . According to the study conducted in the Canadian population, patients with allelic polymorphisms (T) variants are associated with a greater sensitivity to warfarin and, therefore, lead to a significant reduction in the weekly dose of warfarin 55 .…”
Section: Discussionsupporting
confidence: 90%
“…Cigarette and air pollution are major sources of lung carcinogens; hence, studies have reported polymorphisms in CYP1A1 , CYP1A2 , CYP2F1 , CYP2A6*2 , and CYP2A6*9 ( 300 305 ) in lung cancer patients in North Africa. These polymorphisms alter the detoxification rate of toxicants, and individuals who carry the slow metabolizer variants have an increased risk of lung cancer ( 300 ). For example, Hussein et al ( 302 ) concluded that Egyptian smokers with CYP1A1 m1 (rs4646903) and CYP1A1 m2 (rs1048943) are more likely to develop squamous cell carcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…The lung cancer cases in most of these studies included a mixture of smokers and never smokers (typically defined as smoking <100 per lifetime) and, as would be expected, the significance of the protective effect was attenuated if it was not stratified by smoking status (149,150). A few studies have found no relationship between CYP2A6 genotype and lung cancer risk (151,(156)(157)(158). However, the majority, if not all, of these negative studies are due to the inclusion of never smokers or to an insufficient number of cases.…”
Section: Relationship Of Cyp2a6 and Nicotine Metabolism To Lung Cancermentioning
confidence: 99%